Exploration of a Fast Pathway to Nuclear Fusion: Thermal Analysis and Cooling Design Considerations for the ARC Reactor. (2nd January 2020) - Segantin, S.; Testoni, R.; Hartwig, Z.; Whyte, D.; Zucchetti, M.
Abstract: Progress in technological fields such as high-temperature superconductors, additive manufacturing, and innovative materials has led to new scenarios and to a second generation of fusion reactor designs. The new Affordable Robust Compact (ARC) fusion reactor, which compared to other designs meets its goal to achieve fusion energy in a less expensive, smaller but even more powerful, faster way, has been designed at Massachusetts Institute of Technology. In order to define ARC's role in future electricity grids, a feasibility investigation of the load-following concept has been carried out, starting on ARC's vacuum vessel (VV), which is the component closest to the plasma. Finite element analysis models have been designed, and thermomechanical analyses have been conducted. In this framework thermal fatigue and creep remain the main issues. This study identifies and verifies a suitable temperature range for the VV coolant. Indeed, it is found to satisfy both requirements for the lifetime of the structural material and thermodynamic efficiency optimization.